2022
DOI: 10.1021/acsnano.2c05570
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Synthesis and Characterizations of Atomically-Thin Nickel Tellurides with Versatile Stoichiometric Phases through Self-Intercalation

Abstract: Self-intercalation of native metal atoms in two-dimensional (2D) transition metal dichalcogenides has received rapidly increasing interest, due to the generation of intriguing structures and exotic physical properties, however, only reported in limited materials systems. An emerging type-II Dirac semimetal, NiTe2, has inspired great attention at the 2D thickness region, but has been rarely achieved so far. Herein, we report the direct synthesis of mono- to few-layer Ni-tellurides including 1T-NiTe2 and Ni-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…The evolution of those superstructures upon postannealing confirms the instability of the 4 × 4, 4 × 1, and 28 × 28 phases, which was further verified by another postannealing process on the sample grown at 300 °C (see Figure S3 for details). In Supporting Note 1, we show that the Te-deficiency-induced structural changes and the interfacial intercalation are not readily observed and unlikely to exist.…”
Section: Resultsmentioning
confidence: 83%
“…The evolution of those superstructures upon postannealing confirms the instability of the 4 × 4, 4 × 1, and 28 × 28 phases, which was further verified by another postannealing process on the sample grown at 300 °C (see Figure S3 for details). In Supporting Note 1, we show that the Te-deficiency-induced structural changes and the interfacial intercalation are not readily observed and unlikely to exist.…”
Section: Resultsmentioning
confidence: 83%
“…Interestingly, Ni x Te y compounds in the other ratios of Ni and Te also appeared in this process, which indicated that self-intercalation occurred in these finished products. 73 In the CVD process, the key to achieving uniform large nanosheets lies in the lattice matching between the synthesized 2D material and the substrate. This is depicted in Fig.…”
Section: Preparation Methods Of Tmdsmentioning
confidence: 99%
“…[ 85 ] Particularly, the structures of M 3 Te 4 were also observed in Cr‐ and V‐ tellurides. [ 86 ] Differing from the Cr‐ and V‐based intercalated crystals, Ni‐based intercalated crystals Ni 3 Te 4 and Ni 5 Te 6 are formed due to the high metal chemical potential under Ni‐rich conditions, [ 87 ] as shown in Figure 5f,g. According to the intercalation concentration, 2/3 layer (≈66.7%) of Ni intercalation endows a Ni 5 Te 6 phase, while 1/2 layer (≈50%) of Ni intercalation results in Ni 3 Te 4 .…”
Section: Synthetic Strategies Of the 2d Materialsmentioning
confidence: 99%
“…Panels (f) and (g) reproduced with permission. [ 87 ] Copyright 2022, American Chemical Society. h) Schematic illustration of pristine TaS 2 and self‐intercalated Ta 7 S 12 by MBE under a low and a high Ta‐flux environment, respectively.…”
Section: Synthetic Strategies Of the 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation